2021
DOI: 10.22271/phyto.2021.v10.i3c.14073
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effect of two invasive weeds on growth performance of Sorghum vulgare Pers

Abstract: The present study reveals allelopathic potential of aqueous leaf extracts of two invasive weeds Euphorbia hirta L. and Parthenium hysterophorus L. on seed germination, growth performance and protein content of jowar (Sorghum vulgare Pers.) seedlings. Laboratory experiments were conducted to check the allelopathic potential of aqueous extract of selected weeds on germination and seedling growth of jowar. Enfluence of aqueous extrats (25, 50, 75 and 100 % concentrations) of two weed plants were studied on seed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The Jowar seeds maximum root and shoot length was observed in 25% concentration of Parthenium leaf extracts, i.e 5.23 cm and 9.25 cm, respectively, whereas in control root and shoot length Ghodake et al (2012) reported that allelopathic effect of three Euphorbia species on seed germination and seedling growth of wheat. These observations are in agreement with the findings of earlier workers Mali et al (2021), who reported that the effect of P.hysterophorous L. root growth of Jowar indicted stimulatory effects with respect to concerned concentration of extracts while in case of shoot growth, 50% and 100 % concentrations lower plumule.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The Jowar seeds maximum root and shoot length was observed in 25% concentration of Parthenium leaf extracts, i.e 5.23 cm and 9.25 cm, respectively, whereas in control root and shoot length Ghodake et al (2012) reported that allelopathic effect of three Euphorbia species on seed germination and seedling growth of wheat. These observations are in agreement with the findings of earlier workers Mali et al (2021), who reported that the effect of P.hysterophorous L. root growth of Jowar indicted stimulatory effects with respect to concerned concentration of extracts while in case of shoot growth, 50% and 100 % concentrations lower plumule.…”
Section: Resultssupporting
confidence: 93%
“…Similar to these results Jondhale and Chavan (2021) recorded fresh weight of seedling, which varied from 1.6 to 2.7 g and 1.3 to 2.7g in different concentrations of C.dactylon and P. hysterophorous, respectively as compared to 2.7g in the control. These results are in conformity with the findings of Mali, et al (2021), who observed that higher concentrations of leaf extract of P.hysterophorus reduced seed germination and seedling growth and weight in sorghum. The observations recorded in the present investigation are in conformity with the findings of Mali and Kanade (2014) who found that the aqueous leaf extracts of A. sessilis, (L.) R.Br and C. dactylon (L.) Pers.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The stimulatory or inhibitory effects of allelopathic chemicals depend on the concentration and composition of the released compounds in the environment (AL-Jobori and Ali 2014). Allelochemicals with harmful allelopathic properties are a vital component of plant resistance against herbivory (Mali et al 2021). Allelopathy has also been effective in controlling stored grain and field crops from pests and several pathogens.…”
Section: Introductionmentioning
confidence: 99%